Isolated traumatic brain injury results in significant pre-hospital derangement of cardiovascular physiology. Issue 9 (September 2018) - Gavrilovski, M.; El-Zanfaly, M.; Lyon, R.M.
Abstract: Introduction: Major trauma can result in both life-threatening haemorrhage and traumatic brain injury (TBI). The pre-hospital management of these conditions, particularly in relation to the cardiovascular system, is very different. TBI can result in cardiovascular instability but the exact incidence remains poorly described. This study explores the incidence of cardiovascular instability in patients undergoing pre-hospital anaesthesia for suspected TBI. Methods: Retrospective case series of all pre-hospital trauma patients attended by Kent, Surrey & Sussex Air Ambulance Trust (United Kingdom) trauma team during the period 1 January 2015–31 December 2016. Patients were included if they showed clinical signs of TBI, underwent pre-hospital anaesthesia and hospital computed tomography scanning subsequently confirmed an isolated TBI. Results: Out of 121 patients with confirmed isolated TBI, 68 were cardiovascularly stable throughout the pre-anaesthesia phase, whilst 53 (44%) showed signs of instability (HR > 100bpm and/or SBP < 100 mmHg pre-anaesthesia). Hypotension (SBP < 100) with or without tachycardia was present in 14 (12%) patients. 10 (8%) patients with isolated TBI received pre-hospital blood product transfusion. Conclusion: Increased awareness that traumatic brain injury can cause significant derangement to heart rate and blood pressure, even in the absence of major haemorrhage, would allow the pre-hospital clinician to treat cardiovascular instability with the most appropriate means, such as crystalloid and vasopressors, to limit secondary brain injury.